The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1631/jzus.2006.b0749
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone protects PC12 cells from ischemic-like injury via attenuating the damage to mitochondria

Abstract: Background: Edaravone had been validated to effectively protect against ischemic injuries. In this study, we investigated the protective effect of edaravone by observing the effects on anti-apoptosis, regulation of Bcl-2/Bax protein expression and recovering from damage to mitochondria after OGD (oxygen-glucose deprivation)-reperfusion. Methods: Viability of PC12 cells which were injured at different time of OGD injury, was quantified by measuring MTT (2-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
3
11
1
Order By: Relevance
“…ED decreased METH induced ROS production and also significant decreased in LPO and PC content compared with METH treated group. Our data was consistent with previous studies that reported antioxidant and radical scavenging effects of ED (35,36). High level of ROS in cell can damage cell and organelle membrane such as mitochondrial membrane which could triggering cell death signaling that finally could lead to several pathological conditions such as myocardial infarction (37,38).…”
Section: Discussionsupporting
confidence: 93%
“…ED decreased METH induced ROS production and also significant decreased in LPO and PC content compared with METH treated group. Our data was consistent with previous studies that reported antioxidant and radical scavenging effects of ED (35,36). High level of ROS in cell can damage cell and organelle membrane such as mitochondrial membrane which could triggering cell death signaling that finally could lead to several pathological conditions such as myocardial infarction (37,38).…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that the mechanisms of the protective effect involve inhibition of the activation of microglia [10,11] and astrocytes [10], and protection against endothelial cell injury [12], as well as the inhibition of cerebral edema [13]. Regarding the effect on the neurons themselves, it has been reported that cultured hippocampal neurons and neuronal PC 12 cells treated with edaravone were protected against glucose-oxygen deprivation [14,15]. However, as far as we know, there have been no reports about the effect of edaravone on neurons themselves against glutamate neurotoxicity, i. e., excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ROS is an important cause of cell death. Studies have indicated that many free radical scavengers attenuate cell death after OGD (Zhang et al 2008; Song et al 2006; Wu et al 2006). Direct 20-5,14–HEDGE-induced ROS generation and HET0016-attenuated ROS production after OGD in cultured neurons, and the similar neuroprotection provided by HET0016 and 20-HETE antagonist 20-6,15–HEDGE support the view that 20-HETE contributes to the adverse effects after OGD.…”
Section: Discussionmentioning
confidence: 99%